Effect of selenium supplementation on the development of Hashimoto thyroiditis - a review of the literature - Justyna Sak; Michał Nowiński; Laura Fus-Mazurkiewicz; Wojciech Mazurkiewicz; Dominika Król (Termedia Publishing House, 2024)
Hashimoto's thyroiditis is the most common cause of hypothyroidism. The disease causes interstitial degradation of the gland by mononuclear cells. It appears that one of the organs most sensitive to selenium deficiency may be the thyroid gland. Studies confirm that selenium deficiency adversely affects its function. Insufficient selenium in the body can impair immune function, which seems to be a very important aspect in Hashimoto's thyroiditis. However, experiments conducted by researchers around the world indicate the need for proper use of selenium preparations. Like any element, its improper use can prove toxic to the body. Incorporating selenium into the treatment of Hashimoto's disease can bring many benefits, provided the patient's health history is carefully reviewed.